新加坡5岁至6岁英汉双语儿童 汉语用工具手部动作动词的应用特征 = A study on the application of Chinese hand action verbs with tools by English-Chinese bilingual children aged 5-6 in Singapore - 苏嘉盈 Soh, Veronica Jia Ying (Nanyang Technological University, 2020)
儿童语言习是语言学领域备受关注的课题之一。关于儿童语言习得的研究不少，但是关于双语儿童对汉语用工具手部动作动词的研究却比较有限。本研究探讨的汉语用工具手部动作动词是指需要工具才能够完成某动作的动词，如‘剪’。由于这类动词是日常生活中接触频率较高的词类之一，因此儿童对这类动词的掌握程度极其重要。本研究希望考察新加坡5-6岁英汉双语儿童对不同汉语用工具手部动作动词的理解并掌握他们使用这类动词的应用特征。这项研究也希望通过儿童对不同媒介内容的描述，考察其华语语言能力，从而探索更有效的教学媒介以帮助儿童学习华语。 本研究从Gao（2001）的身体动作动词表中选用三个用工具手部动作动词‘剪’、‘切’和‘削’作为研究主要目标。本研究主要分成两个部分：（1）通过家长问卷调查理解儿童家庭背景以及（2）一项为儿童设计的口语测试。根据所取得的儿童语料，我们对其应用这些动词的特征展开分析讨论。研究结果发现，新加坡5-6岁的英汉双语儿童普遍展现中等至上等的华语表达能力，而这与其日常接触该语言的频率息息相关。此外，儿童的相关经验也会影响他们对事物的联想能力及其描述的完整性。本文引用了测试收集的实际语料作为例子，深入探讨新加坡5-6岁的英汉双语儿童使用汉语用工具手部动作动词时所出现的应用特征。 本研究希望通过此调查结果理解新加坡5-6岁英汉双语儿童对汉语用工具手部动作动词的应用特征以及影响其语言能力的相关因素。通过对这方面的理解，家长与研究者也能够思考如何帮助儿童提升其对这类动词的掌握程度。儿童对不同媒介内容的描述也有助于本地教育者理解更适合儿童的教学媒介，从而改善其教学方式以帮助儿童学习华语。 Child language acquisition has always been a popular topic in the linguistics field. Many studies on child language acquisition can be found, but studies on the application of Chinese hand action verbs with tools, particularly by bilingual children are rare. Chinese hand action verbs with tools refers to action verbs which requires a tool to complete an action, such as ‘cut’. Children’s acquisition of these Chinese hand action verbs is important as they are commonly used in our daily lives. Therefore, this study aims to understand the application of Chinese hand action verbs with tools by Singaporean English-Chinese bilingual children aged 5 and 6 years old. The study also intends to examine their general language competence in linguistic output stimulated by audio and video input (e.g., describing picture and videos’ contents), to explore effective medium for children to learn Chinese. This study’s experiment was designed using 3 basic hand action verbs with instruments from Gao’s (2001) physical action verb list. There are two parts in the design of the study: (1) a questionnaire for children’s parents to provide demographic information of their families and (2) a verbal language test designed in a child-friendly fashion for the children to complete. The overall findings showed that most Singaporean 5 and 6 year old English-Chinese bilingual children possess average and excellent language competence in linguistic output. This finding had been found to be closely related to the frequency of children’s daily contact with the language. Besides that, the findings have also showed that children’s relevant experience of things does affect their ability to associate relevant content and the completeness of their descriptions. This thesis will make use of the actual corpus collected during the verbal test as an example, to explore the application characteristics of Singaporean 5 and 6 year old English-Chinese bilingual children using these Chinese hand action verbs. By understanding the factors affecting children’s application of Chinese hand action verbs with tools, parents and researchers can brainstorm on ideas to enhance children’s degree of verb acquisition. By understanding the more effective medium in helping children to learn Chinese, local educators will also be able to improvise on teaching methods in school to help children to acquire general content more effectively.